Taxonomic revision of Mesamphiagrion Kennedy, 1920 from Colombia (Odonata: Coenagrionidae), with the description of four new species - Bota-Sierra, Cornelio Andrés; Echeverri, Martha Isabel Wolff (Zootaxa, 2013)
The genus Mesamphiagrion Kennedy, 1920, occurs in the Pantepui region and northern Andes in South America and is most speciose in Colombia where the genus is less known. In this work, we record 10 species of Mesamphiagrion from Colombia, including four new species (Mesamphiagrion gaudiimontanum Bota-Sierra sp. nov., M. nataliae Bota-Sierra sp. nov., M. rosseri Bota-Sierra sp. nov., and M. santainense Bota-Sierra sp. nov.). We also redescribe the male of M. risi (De Marmels 1997) and describe the females of M. risi, M. ovigerum (Calvert, 1909), and M. occultum (Ris, 1918), which were previously unknown. Descriptions, photographs, illustrations, distribution maps, natural history notes, and a diagnostic key for males and females of Mesamphiagrion from Colombia are provided.